The diagnosis and treatment of the acute scrotum in children and adolescents. - Knight, P J (1984)
Diagnosing acute scrotal pain and swelling in children and adolescents is urgent and often difficult. A review of 395 boys hospitalized with acute scrotal pain and/or swelling shows that a useful approach is to divide these patients into four groups--those with intermittent but recurrent episodes of pain, those with pathognomonic physical findings, those with definite epididymitis, and a remaining group with nonspecific swelling and tenderness. Five per cent of boys in this series presented with recurring episodes of scrotal pain; these boys should undergo a simple scrotal operation that yields excellent results. Eight per cent had pathognomonic physical findings; treatment in these boys is straightforward. Eighteen per cent had a definite diagnosis of acute epididymitis (i.e., three nonpathognomonic but suggestive findings of acute epididymitis or two suggestive findings plus a radionuclide scan showing bilateral perfusion); nonoperative therapy is indicated in this group. In the remaining boys, scrotal exploration is the diagnostic (and usually therapeutic) procedure of choice.